Population dynamics of Bactrocera dorsalis (Diptera: Tephritidae) in Lujiangba, Yunnan - CHEN Peng; YE Hui (浙江大学学报. 农业与生命科学版)
Annual monitoring was conducted on the population dynamics of the oriental fruit fly, Bactrocera dorsalis (Hendel) (Diptera: Tephritidae) through methyl eugenol-baited traps all year during 2004—2006 in Lujiangba, Yunnan, China. Temperature, rainfall and host-plant species were analyzed in relation to population fluctuations of the fly. The results indicate that the fruit fly occurs all year around in Lujiangba. The population fluctuation is significantly separated into two periods: a low tide population period from December to next April, and a high tide population period from May to November with high abundance in August in each year. Mango, longan, citrus, papaya, lichee and guava were the most preferred host plants of B. dorsalis in Lujiangba. The planting areas, fruiting periods and productions of these fruits exerted essential effects on the fly population fluctuations, and regarded as one of the important factors affecting the fly population dynamics in the Lujiangba area. Stepwise regression analysis demonstrates that during the period from May to November, monthly mean temperature, monthly mean maximum temperature, monthly rainfall, monthly raining days, monthly sunlight hours and relative humidity synthetically impact the population dynamics, among these factors, monthly raining days and relative humidity are crucial factors affecting the population dynamics. During period from December to next April, monthly mean temperature, monthly mean maximum temperature, monthly sunlight hours and relative humidity synthetically impact the population dynamics, among them, the monthly mean maximum temperature and the monthly mean temperature are the crucial factors affecting the population dynamics.